Effects of functional milk containing galactooligosaccharide, maltitol, and glucomannan on the production of hydrogen gas in the human intestine. (August 2017) - Matsumoto, Mitsuharu; Fujita, Ayako; Yamashita, Ayano; Kameoka, Shoichiro; Shimomura, Yumi; Kitada, Yusuke; Tamada, Hazuki; Nakamura, Shigeru; Tsubota, Kazuo
Highlights: The dietary fibers GOS, maltitol, and glucomannan were evaluated for H2 production. Cows' milk with these dietary fibers was developed as a functional milk. H2 -producing milk consumption increased H2 concentrations in most volunteers. This milk caused sustained H2 production compared with H2 water/normal cows' milk. Abstract: Hydrogen gas (H2 ) reacts with strong oxidants, and the effectiveness of H2 inhalation or ingestion of H2 water has been demonstrated for many diseases. H2 produced by the intestinal microbiome from indigestible components is the major source of exogenous H2 . In this study, we screened a wide variety of indigestible components that induce H2 production by the intestinal microbiome, which exhibits large diversity, and developed a beverage composed of cows' milk with galactooligosaccharide, maltitol, and glucomannan (H2 -producing milk). In clinical trials, the breath H2 concentration of most volunteers was increased by consumption of H2 -producing milk 1 (each material: 1%) and H2 -producing milk 2 (galactooligosaccharide: 1.5%, maltitol: 1%, and glucomannan: 0.1%). The total range of H2 production (area under the curve) increased and a higher peak concentration was observed compared with consumption of H2 water or pure cows' milk. Thus, this material may be a desirable functional milk.